Schemes for the sound transmission of flat, curved and axisymmetric structures excited by aerodynamic and acoustic sources. (15th September 2019) - Errico, F.; Ichchou, M.; Franco, F.; De Rosa, S.; Bareille, O.; Droz, C.
Abstract: The paper describes a methodology for computing the sound transmission loss of any flat, curved and cylindrical, homogeneous and periodic structure, under any type of acoustic and/or aerodynamic load. An approximate excitation model is introduced to reproduce uncorrelated and spatially-correlated loads using a wavenumber integration of surface waves. Then, a wave finite element formulation is developed and interfaced with the excitation models in order to cover industrially-relevant case studies. Analytical, numerical and experimental transmission losses are presented for validation purposes. Finite size effects are also taken into account using a spatial windowing and a cylindrical analogy, for curved structures. Different periodic-cell designs are also compared and investigated under turbulent boundary layer and diffuse acoustic field excitations.